Analisis Penerapan Standar Akuntansi Keuangan No 16 (Aset Tetap) Pada PT Telkom Indonesia Tbk - Raihan Luida, Amanda; Excelina, Chika; Ilyasa, Helmi; Yulia Amanda, Taniya; Verena V, Vincenthya (Rifa'Institute, 2022)
Good or bad economic growth can be seen in the financial statements, namely the balance sheet and seen from the total value of fixed assets. This is usually a consideration for internal or external parties in making decisions. Assets are very important things owned by the company. In the company's operational activities, fixed assets have a very significant role in producing goods and services, providing benefits to the company and to achieve company goals. This means that decision makers really need information related to fixed assets in the company. These decision makers need information related to accounting for fixed assets in accordance with accounting theory based on Statement of Financial Accounting Standards (PSAK) No. 16 in the company's activities. The research method used in this research is descriptive analysis method with quantitative shortness. From the results of the study it can be concluded that PT Telkom Indonesia Tbk in its scope is not in accordance with PSAK No. 16, measurement and depreciation of property, plant and equipment in accordance with PSAK No. 16.